Co-integration between Malaysia stock market, ASEAN and ASEAN plus three countries during pre and post 14th Malaysia’s general election using Johannsen co-integration test / Muhammad Akmal Hakim Bohari - Bohari, Muhammad Akmal Hakim (2022)
The study aims to know whether there exists a link between Malaysia stock market with other ASEAN (Indonesia, Singapore, Thailand, Vietnam and Philippines) and ASEAN plus three stock markets (China, Japan and Korea) before and after the 14th Malaysian General Election held on 9 May 2018. This study ran the correlation test to determine the relationship between the stock markets and as a result, the correlation between the stock markets increased after the General Election. This research further ran the Johansen Co-integration test to study the linkages. This research found that the co-integration between the variables exist. To study more in depth, this research ran the Granger-causality test. There are a few markets that have co-integrating factors with Malaysia’s stock market before and after the General Election. The study on the co-integration can provide potential benefits for stakeholders who invested in the stock markets by enhancing their risk appetite in investing.